Dynamic crosslinking green binder for silicon-based negative electrode of lithium ion battery as well as preparation and application of dynamic crosslinking green binder

Through the design of PAA-ST composite adhesive, combined with nano-silicon particles and conductive carbon black, a dynamic cross-linking network is formed, which solves the stability and environmental friendliness of the silicon-based anode of lithium-ion batteries, and significantly improves the battery circulation and Rate performance, achieving high specific capacity and low cost battery performance.

CN119161829APending Publication Date: 2024-12-20SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411197745.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The adhesive design of silicon-based anode of traditional lithium-ion batteries has problems such as insufficient linear structure, high cost, poor environmental pollution and poor stability, especially the volume changes and powdering problems caused by the charge and discharge of silicon negative electrodes are difficult to effectively solve.

Method used

Using PAA-ST composite binder, by stirring and mixing polyacrylic acid and starch powder in water, forming a composite glue solution with reversible hydrogen bonds, combining nano-silicon particles and conductive carbon black to form a dynamic cross-linking network to improve the silicon-based negative electrode bonding properties.

Benefits of technology

It has achieved low-cost, environmentally friendly water-soluble polymer binder, significantly improved the circulation performance and rate performance of the silicon-based negative electrode, maintained high specific capacity and excellent electrochemical performance, and significantly improved the first discharge capacity and circulation capacity. The polarization is much better than traditional silicon negative electrode batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161829A_ABST
    Figure CN119161829A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium ion battery binder materials, and discloses a dynamic crosslinking green binder for a silicon-based negative electrode of a lithium ion battery as well as preparation and application of the dynamic crosslinking green binder. The preparation method of the binder comprises the following steps: uniformly stirring and mixing polyacrylic acid powder and starch powder in water to prepare a PAA-ST compound glue solution, namely the PAA-ST composite binder. The silicon negative electrode half cell of the PAA-ST-3 still keeps the excellent performance of 2405mAh / g high reversible specific capacity after being cycled for 100 times under the current density of 840mA / g. In addition, the initial discharge capacity of the silicon negative electrode half cell of PAA-ST-3 can reach 3804mAh / g of mass specific capacity and nearly 92% of initial coulombic efficiency, which is far superior to the initial coulombic efficiency of many current silicon negative electrode cells. Meanwhile, the battery made of the binder is small in polarization, and the optimization degree of the battery is also explained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery binder materials, and particularly relates to a dynamic cross-linking green binder for a silicon-based negative electrode of a lithium ion battery and a preparation method and application thereof. Background Art

[0002] With the proposal of the "dual carbon target", the demand for electric vehicles and other fields has increased, which has greatly promoted the update and iteration of energy storage batteries. Currently, the most mature batteries put into the market are still lithium-ion batteries. In the development of lithium-ion batteries, how to improve their energy density has become a top priority for people's research. The energy density depends on the capacity of the active material on the battery electrode. The research on positive electrode materials has entered a bottleneck period. Researchers have turned their attention to negative electrode materials, pursuing higher capacity negative electrode materials to obtain larger capacity batteries. At present, compared with the commercial graphite negative electrode with a mass specific capacity of only 372mAh / g, the capacity of silicon is as high as 4200mAh / g. At the same time, its moderate voltage platform (<0.5V vs.Li + / Li) and high natural abundance make it one of the best candidates for the promising new generation of lithium-ion battery negative electrode materials. However, silicon as a negative electrode undergoes huge volume changes during the charge and discharge process due to continuous lithium insertion and removal, which in turn causes silicon pulverization, leading to silicon electrode cracking, thickness growth, and continuous solid electrolyte interface growth, which causes its capacity to decay rapidly.

[0003] In addition to electrode material development and electrolyte optimization, binder design is considered to be a cost-effective strategy to improve the structural stability of silicon-based electrodes. The traditional battery binder polyvinylidene fluoride (PVDF) is no longer suitable for silicon anodes due to its linear structure and weak van der Waals interaction. In addition, it requires the organic solvent NMP as a solvent during its use, which is no longer in line with the current green development theme. Therefore, relatively environmentally friendly water-based binders such as polyacrylic acid (PAA) have begun to enter the field of vision of researchers. PAA has excellent self-healing properties and can modify the microcracks generated during battery charging and discharging by forming dynamic covalent bonds or hydrogen bonds. Compared with PVDF, it can improve the stability of silicon-based anodes to a certain extent, but there are still certain limitations to keep silicon anodes in long-term stable high-performance cycles. Therefore, it is of great significance to develop new and efficient silicon-based anode polymer binders for lithium-ion batteries. Summary of the invention

[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, and to address the problems of poor adhesion, high cost and environmental pollution caused by the single linear structure of traditional adhesives, the primary purpose of the present invention is to provide a method for preparing a PAA-ST composite adhesive, which has simple synthesis conditions, high raw material safety and low price, and meets the requirements of green chemistry.

[0005] Another object of the present invention is to provide a PAA-ST composite adhesive prepared by the above method. The adhesive has a large number of carboxyl groups and hydroxyl groups to form reversible hydrogen bonds between molecules, and the composite also has a certain hydrogen bond effect with the silicon surface. The three form a dynamic cross-linked network, which makes it have excellent bonding properties. It is a low-cost, environmentally friendly water-soluble polymer adhesive.

[0006] Another object of the present invention is to provide application of the above-mentioned PAA-ST composite binder in silicon-based negative electrodes.

[0007] Another object of the present invention is to provide a silicon-based negative electrode using the above-mentioned binder.

[0008] Another object of the present invention is to provide the application of the above-mentioned silicon-based negative electrode in lithium-ion batteries. When the composite binder is mixed with nano silicon particles (SiNPs) and conductive carbon black Super P (SP) in a certain proportion to prepare an electrode, the obtained silicon negative electrode half-cell exhibits good cycle performance and rate performance. Among the optimized components, the silicon negative electrode half-cell of PAA-ST-3 (i.e., PAA:ST=7:3 (wt%)) maintains an excellent performance of a high specific capacity of 2405 mAh / g after 100 cycles at a current density of 840 mA / g.

[0009] The purpose of the present invention is achieved through the following solutions:

[0010] A method for preparing a PAA-ST composite adhesive comprises the following steps: stirring and mixing polyacrylic acid (PAA) powder and starch (ST) powder in water to obtain a PAA-ST composite adhesive solution, namely, the PAA-ST composite adhesive.

[0011] The molecular weight of the polyacrylic acid powder is 10w-50w, preferably 450000.

[0012] The starch is preferably corn starch.

[0013] The mass ratio of the polyacrylic acid powder to the starch powder is 10-5:0-5, and the starch content cannot be 0, preferably 9:1-5:5, and more preferably 7:3.

[0014] The amount of water used is sufficient to completely dissolve the PAA powder and the ST powder in the water. Preferably, 0.2-0.5 mL of water is added to every 45 mg of the raw material, wherein the mass of the raw material is the total mass of the PAA powder and the ST powder.

[0015] The stirring and mixing is preferably carried out at a rotation speed of 300-1000 rpm for 1-12 hours to ensure uniform mixing.

[0016] A PAA-ST composite adhesive prepared by the method.

[0017] The application of the above-mentioned PAA-ST composite binder in the silicon-based negative electrode of lithium-ion batteries.

[0018] A lithium ion battery silicon-based negative electrode containing the above composite binder is prepared by the following method:

[0019] (1) After the dried nano-silicon negative electrode powder and the conductive agent are mixed evenly, the PAA-ST composite binder is added, and the mixture is stirred and mixed evenly to form an electrode slurry;

[0020] (2) The prepared slurry is coated, vacuum dried, and punched to obtain an electrode sheet.

[0021] The conductive agent described in step (1) is at least one of conductive carbon black Super P, C65, and acetylene black.

[0022] The mass ratio of the nano-silicon negative electrode powder, the conductive agent and the PAA-ST composite binder described in step (1) is 6-8:1-2:2-1, preferably 7:1.5:1.5.

[0023] The stirring and mixing in step (1) to form the electrode slurry is preferably carried out at a rotation speed of 300-1000 rpm for 12-24 hours to form the electrode slurry, and is preferably carried out at a rotation speed of 1000 rpm for more than 12 hours to form the electrode slurry.

[0024] Step (1) During the stirring to form the electrode slurry, the consistency of the slurry is adjusted with water in an appropriate amount. The purpose is to make the slurry have a certain fluidity but not too thin or too thick so that it can be better coated on the copper foil to prepare the electrode sheet. Preferably, 0.8-1.2 ml of water is added for every 300 mg of the raw material slurry, wherein the raw material mass refers to the total mass of the nano-silicon negative electrode powder, the conductive agent and the PAA-ST composite binder.

[0025] The above-mentioned lithium-ion battery silicon-based negative electrode is used in lithium-ion batteries.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0027] (1) The present invention uses PAA-ST as a silicon-based negative electrode binder for lithium-ion batteries. The raw materials are cheap and easy to obtain, and the preparation method is simple. It is a type of environmentally friendly aqueous solution polymer composite binder.

[0028] (2) There are multiple layers of hydrogen bonds between the PAA-ST binder and the surface of the nano-silicon particles, forming a dynamic cross-linked network, which gives it better electrochemical properties than PAA itself.

[0029] (3) Under the optimized components, the silicon negative electrode half-cell of PAA-ST-3 maintains the excellent performance of high reversible specific capacity of 2405mAh / g after 100 cycles at a current density of 840mA / g. In addition, the first discharge capacity of the silicon negative electrode half-cell of PAA-ST-3 can reach a mass specific capacity of 3804mAh / g and a first coulombic efficiency of nearly 92%, which is far better than the first coulombic efficiency of many silicon negative electrode batteries today. At the same time, the battery polarization made by the binder is small, which also shows its degree of optimization. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the reversible physical cross-linking network formed by the PAA-ST composite binder in the electrode.

[0031] Figure 2 FTIR, Raman, TG and DSC analysis of PAA-ST binders at different ratios.

[0032] Figure 3 Characterization of the electrochemical performance of silicon negative electrode half-cells with various ratios of Si@PAA-ST, including a) long cycle diagram with a current density of 0.2C; b) first charge and discharge curve; c) rate performance; d) Nengquist curve after 100 cycles of the battery; e) cycle performance of Si@PAA-ST-3 battery at 1C; f) Nengquist curves of Si@PAA-ST-3 battery before cycling, after 50 cycles, and after 100 cycles; d) the first 5 CV scan curves of Si@PAA-ST-3 battery.

[0033] Figure 4 SEM comparison images of the electrode surfaces of Si@PAA-ST electrode sheets of various proportions at different magnification scales before and after 100 cycles, where a) is before the cycle; b) is after 100 cycles. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially. The CAS number of corn starch in the examples is 9005-25-8, and the brand is Adamas.

[0035] The present invention provides Figure 1 Schematic diagram of the reversible physical cross-linked network formed by the PAA-ST composite binder in the electrode is shown to facilitate understanding of the mode of action.

[0036] The following is a method for preparing a PAA-ST composite binder and a lithium-ion silicon negative electrode half-cell therefrom, comprising the following steps:

[0037] (1) PAA powder and PAA:ST powder with a mass ratio of 9:1, 8:2, 7:3, 6:4, and 5:5 were weighed and dissolved in a small amount of deionized water (45 mg of the raw material was dissolved in 0.2 ml of deionized water), and stirred at a speed of 300 rpm for more than 1 hour to prepare PAA glue and PAA-ST composite glue. The molecular weight of the PAA powder is 450,000, and the ST powder is corn starch.

[0038] (2) Add the dried SiNPs and SP into a mortar at a ratio of SiNPs: SP: PAA / PAA-ST = 7:1.5:1.5 (mass ratio) and mix them evenly, then pour them into the above-mentioned binder glue and stir them at a speed of 1000 rpm for more than 12 hours to form an electrode slurry. During this period, deionized water is used to adjust the slurry consistency. Generally, 1.0 ml of deionized water is added for every 300 mg of raw materials. The SiNPs are silicon nanoparticles with a particle size of 80-100 nm, and the SP is conductive carbon black Super P.

[0039] (3) The prepared slurry can be scraped onto copper foil using a scraper with a thickness of 100 μm. After the copper foil is fixed, it is placed in a vacuum drying oven at 100 °C for vacuum drying for 12 h. The dried silicon negative electrode sheet is cut into small discs with a diameter of 12 mm so that it can be placed in button cells for battery assembly. The electrode sheet loading is 0.6 mg / cm 2 .

[0040] (4) The dried electrode sheet is transferred into a glove box. The water oxygen value in the glove box should be less than 0.1ppm. The battery is assembled with a CR2032 battery shell assembly. Starting from the negative electrode shell, it is the negative electrode shell, 0.5mm thick gasket, 15.6mm diameter lithium sheet, 50μL electrolyte, PP / PE / PP diaphragm (16mm diameter), 50μL electrolyte, silicon negative electrode sheet, 0.5mm thick gasket, spring, positive electrode shell. After assembly, the battery is packaged with a hydraulic press. The composition of the electrolyte is: 1.0M LiPF6inEC:DEC:FEC=5:5:1Vol%.

[0041] (5) The assembled battery is placed in the blue electric system channel and the activation, cycle or rate programs are set to perform the corresponding electrochemical tests. The constant current charge and discharge cycle and rate performance tests of the battery are performed on the LANDCT3001A battery test system at room temperature (25°C), and the voltage test range is 0.01~1.5V. The constant current charge and discharge test uses 0.05C (1C = 4200mAh g -1) for the initial two cycles of activation, and the subsequent cycle test was carried out at a rate of 0.2C or 1C. The discharge specific capacity obtained from the test was used to evaluate the electrochemical cycle performance of the battery. The rate performance of the electrode was charged and discharged at different rates from 0.05C, 0.1C, 0.2C, 0.5C to 1.0C, and 5 cycles were cycled at each rate, and finally returned to 0.05C for charge and discharge cycle testing. The cyclic voltammetry curve of the battery was tested using a Bio-logic VMP-300 electrochemical workstation. The scanning voltage range was the same as that of the battery charge and discharge, and the scanning rate was 0.2mV s -1 The electrochemical impedance spectroscopy test was completed on an electrochemical workstation, with a test frequency range of 100mHz to 100kHz and a disturbance voltage amplitude of 5mV.

[0042] Example 1

[0043] First, 45.0 mg of PAA powder was dissolved in 0.2 ml of deionized water and stirred thoroughly to obtain a transparent and viscous PAA solution. Figure 2 ;

[0044] 210 mg SiNPs and 45.0 mg Super P were mixed in an agate mortar and added to the above solution. Deionized water was added to make the total water volume 1.0 ml. The mixture was stirred at 1000 rpm for 12 h to form a uniform slurry.

[0045] The slurry was coated on copper foil with a thickness of 100 μm, vacuum dried at 100 °C for 12 h, and then cut into electrode discs with a diameter of 12 mm for standby use. The electrode loading was 0.6 mg / cm 2 ;

[0046] Assemble the battery according to step (4) above and perform post-assembly testing according to step (5) above.

[0047] The test results of the lithium-ion battery (Si@PAA) are as follows: the initial coulombic efficiency is 86%, the initial discharge capacity is 3400mAh / g, and after 100 charge and discharge cycles at a current of 0.2C, the battery capacity is only 1340mAh / g. Figure 3 a) and b) as shown; and its rate performance (such as Figure 3 c) and the impedance after 100 cycles (as shown in Figure 3 As shown in d), they all clearly show poor rate performance and large impedance. Figure 4 It can also be clearly seen that the cracks in the pole pieces are larger before and after the cycle.

[0048] Example 2

[0049] The preparation method of the binder and its silicon negative electrode half-cell is the same as that of Example 1, except that 45.0 mg of PAA powder is replaced by 40.5 mg PAA and 4.5 mg ST to obtain a PAA-ST-1 composite adhesive.

[0050] The test results of the Si@PAA-ST-1 negative electrode half-cell are as follows: the first coulombic efficiency is 92%, the first discharge specific capacity is 3533mAh / g, and after 100 charge and discharge cycles at a current of 0.2C, the battery capacity is still 2055mAh / g. Figure 3 a) and b) as shown; and its rate performance (such as Figure 3 c) and the impedance after 100 cycles (as shown in Figure 3 As shown in d), they all clearly show better rate performance and smaller impedance than Si@PAA. Figure 4 It can also be clearly seen that the cracks in the pole piece have been reduced before and after the cycle.

[0051] Example 3

[0052] The preparation method of the binder and the silicon negative electrode half-cell thereof is the same as that of Example 1, except that 45.0 mg of PAA powder is replaced with 36.0 mg of PAA and 9.0 mg of ST to obtain a PAA-ST-2 composite adhesive.

[0053] The test results of the Si@PAA-ST-2 negative electrode half-cell are as follows: the first coulombic efficiency is 91%, the first discharge specific capacity is 3542mAh / g, and after 100 charge and discharge cycles at a current of 0.2C, the battery capacity is still 2206mAh / g. Figure 3 As shown in a) and b).

[0054] Example 4

[0055] The preparation method of the binder and the silicon negative electrode half-cell thereof is the same as that of Example 1, except that 45.0 mg of PAA powder is replaced with 31.5 mg of PAA and 13.5 mg of ST to obtain a PAA-ST-3 composite adhesive.

[0056] The test results of the Si@PAA-ST-3 negative electrode half-cell showed the best performance, with an initial coulombic efficiency of 92% and an initial discharge capacity of 3804 mAh / g. After 100 charge and discharge cycles at a current of 0.2C, the battery capacity was still 2405 mAh / g. Figure 3 Si@PAA-ST-3 exhibits the best rate performance and the smallest loop impedance, as shown in a) and b). Figure 3 In addition, Figure 3e), this type of battery can still maintain a mass specific capacity of nearly 2000mAh / g after 100 charge and discharge cycles at a high current of 1C, and Figure 3 From the CV diagram of g), we can see that the redox peak difference is small, that is, the polarization is small, which is beneficial to the battery cycle.

[0057] Example 5

[0058] The preparation method of the binder and the silicon negative electrode half-cell thereof is the same as that of Example 1, except that 45.0 mg of PAA powder is replaced with 27.0 mg of PAA and 18.0 mg of ST to obtain a PAA-ST-4 composite adhesive.

[0059] The test results of the Si@PAA-ST-4 negative electrode half-cell are as follows: the first coulombic efficiency is 91%, the first discharge specific capacity is 3548mAh / g, and after 100 charge and discharge cycles at a current of 0.2C, the battery capacity is only 1975mAh / g. Figure 3 As shown in a) and b).

[0060] Example 6

[0061] The preparation method of the binder and the silicon negative electrode half-cell thereof is the same as that of Example 1, except that 45.0 mg of PAA powder is replaced with 22.5 mg of PAA and 22.5 mg of ST to obtain a PAA-ST-5 composite adhesive.

[0062] The test results of the Si@PAA-ST-5 negative electrode half-cell are as follows: the first coulombic efficiency is 91%, the first discharge specific capacity is 3213mAh / g, and after 100 charge and discharge cycles at a current of 0.2C, the battery capacity is only 1910mAh / g. Figure 3 As shown in a) and b).

[0063] Example 7

[0064] The preparation method of the binder and the silicon negative electrode half-cell thereof is the same as that of Example 1, except that 45.0 mg of PAA powder is replaced with 45.0 mg of ST to obtain ST glue solution.

[0065] The test results of the Si@ST negative electrode half-cell are as follows: the first coulombic efficiency is 65.92%, the first discharge specific capacity is 698.6 mAh / g, and after 100 charge and discharge cycles at a current of 0.2C, the battery capacity drops rapidly to only 40.19 mAh / g. Figure 3 As shown in a) and b).

[0066] The above experiments prove that the negative electrode half-cells of Si@PAA and Si@ST have certain disadvantages in terms of first coulomb efficiency, first discharge specific capacity, or cycle and rate performance. The binder obtained by modifying PAA with the addition of ST can not only greatly reduce the battery cost, but also change the thermal stability and chain flexibility of the PAA binder. In addition, due to the formation of a multiple hydrogen bond dynamic cross-linking network in the electrode system, the performance of the battery in all aspects is improved, especially the optimal ratio of Si@PAA-ST-3. This invention has greatly broadened the design ideas of silicon negative electrode binders and provided new possibilities for the commercial application of silicon-based negative electrodes in lithium-ion batteries.

[0067] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a PAA-ST composite binder, characterized in that The method comprises the following steps: mixing polyacrylic acid powder and starch powder in water evenly to prepare PAA-ST composite glue, namely PAA-ST composite adhesive.

2. The method for preparing the PAA-ST composite adhesive according to claim 1, characterized in that: The molecular weight of the polyacrylic acid powder is 10w-50w; The starch is corn starch.

3. The method for preparing the PAA-ST composite adhesive according to claim 1, characterized in that: The mass ratio of the polyacrylic acid powder to the starch powder is 10-5:0-5, and the starch content cannot be 0, preferably 9:1-5:5, and more preferably 7:

3.

4. The method for preparing the PAA-ST composite adhesive according to claim 1, characterized in that: The amount of water used is sufficient to completely dissolve the polyacrylic acid powder and the starch powder in water; preferably, every 45 mg of the raw material is added to 0.2-0.5 mL of water, wherein the mass of the raw material is the total mass of the polyacrylic acid powder and the starch powder.

5. The method for preparing the PAA-ST composite adhesive according to claim 1, characterized in that: The stirring and mixing is stirring at a rotation speed of 300-1000 rpm for 1-12 hours to mix well.

6. A PAA-ST composite adhesive prepared according to the method according to any one of claims 1 to 5.

7. Use of the PAA-ST composite binder according to claim 6 in a silicon-based negative electrode of a lithium-ion battery.

8. A lithium-ion battery silicon-based negative electrode, characterized in that Prepared by the following method: (1) After the dried nano-silicon negative electrode powder and the conductive agent are mixed evenly, the PAA-ST composite binder according to claim 6 is added, and the mixture is stirred and mixed evenly to form an electrode slurry; (2) The prepared slurry is coated, vacuum dried, and punched to obtain an electrode sheet.

9. The lithium-ion battery silicon-based negative electrode according to claim 8, characterized in that: The mass ratio of the nano silicon negative electrode powder, the conductive agent and the PAA-ST composite binder described in step (1) is 6-8:1-2:2-1; Step (1) During the stirring to form the electrode slurry, the slurry consistency is adjusted with water. For every 300 mg of raw material slurry, 0.8-1.2 ml of water is added, wherein the raw material mass refers to the total mass of the nano-silicon negative electrode powder, the conductive agent and the PAA-ST composite binder.

10. Use of the lithium ion battery silicon-based negative electrode according to claim 8 or 9 in lithium ion batteries.

Citation Information

Patent Citations

  • Modified biomass lithium ion battery adhesive

    CN103337656A

  • Lithium ion battery negative electrode polymer binder and preparation method and application thereof

    CN112259734A